Long persistent and photostimulated luminescence properties of Sr2Al2SiO7：Eu2＋/Tm3＋ phosphors - 齐野 张金苏 于洪全 孙佳石 李香萍 程丽红 陈宝玖 (Journal of rare earths, 2016)
A series of Sr2A12SiO7 phosphors with fixed Eu2＋ concentration and various Tm3＋ concentrations were synthesized via a high temperature solid state reaction. The structure and luminescence properties of the samples were characterized by X-ray powder diffraction （XRD）, photoluminescence （PL） spectra, decay curves, thermoluminescence （TL） glow curves as well as the photostimu- lated luminescence （PSL） spectra. Sr2A12SiO7：Eu2＋,Tm3＋ phosphors exhibited strong green phosphorescence and photostimulated lu- minescence originating from 4f65d1-4f7 transition of Eu2＋ after ultraviolet light stimulation. Deep traps were found by analyses on the phosphorescence decays and thermoluminescence spectra. It was also found that with increasing the time interval between UV excita- tion turn-off and stimulation turn-on, the photostimulated luminescence became stronger. This phenomenon resulted from the fact that the captured electron was retrapped by the deep traps. Compared with the Tm3＋-free sample, it was found that the PSL intensity was strongly enhanced in Tm3＋ eodoping samples.